RESPONSABILITÉ PENALE DES PERSONNES MORALES EN DROIT POSITIF CONGOLAIS: APPROCHE COMPARATIVE EN DROIT BELGE ET FRANÇAIS - Gracias OTEMIKONGO MANDEFU; Jean-Paul BINDUBUBI MUNEMEH; MANDEFU, Socrate LISANGA (IJRDO Journal of Law and Cyber Crime, 2020)
Is there a criminal liability of legal persons in Congolese positive law? The decree of January 30, 1940 on the Congolese penal code as amended and supplemented by law n ° 06/018 of July 20, 2006, is silent on this issue. However, case law is divided on this notion. For a long time, only the leaders were prosecuted since the legal person was struck by absolute criminal irresponsibility. This question which creates a great doctrinal controversy has aroused our attention in the present reflection. As a result, on the one hand, we have supporters of the criminal irresponsibility of legal persons forming the minimalist tendency based on the theory of fiction, thus highlighting the fictitious character of legal persons in order to finally defend their argument of the ’irresponsibility. For them, the condition of accountability requires that the author have the intelligence and will. This accountability is only possible to natural persons. Because no moral person has a real existence to possess an intellectual faculty, let alone a will. In addition to the supporters of criminal responsibility: the moral persons are not only fictitious and abstract beings, but have a real existence, which is manifested by concrete structures, of these structures will emerge a will. And this decision of will must be considered as specific to the legal person and distinct from the will of the natural persons who compose them. And if that decision constituted an offense, then the legal person will be held criminally responsible. Proponents of this criminal responsibility form the maximalist tendency and advocate the criminal liability of legal persons on the basis of the theory of the reality of the legal person. In taking part in the debate in our turn, we have considered caressing the maximalist tendency which, on the basis of the theory of the reality of the legal person, recognizes the criminal liability of legal persons, since they are subjects and rights and obligations. Especially since these legal persons are deemed to commit all kinds of offenses as well as natural persons.